Analisis Perbedaan Taktik Konflik pada Dinas Komunikasi dan Informatika Kabupaten Tabalong - Suryani, Lilis (Jurnal PubBis, 2025)
Conflicts in public organizations arise due to complex interactions between bureaucratic actors with diverse backgrounds, interests, and authorities. This creates space for conflict to emerge, either in the form of differences of opinion, conflicting interests, or competition between units and individuals. The Communication and Informatics Office of Tabalong Regency is one of the strategic agencies in supporting digital transformation, public information services, and management of regional government communications. The complexity of tasks and the high intensity of cross-sector coordination make the potential for conflict in this office environment quite high. This study aims to analyze differences in conflict tactics based on gender, worker status and education. This study is a descriptive comparative study with a quantitative approach. The sampling technique uses non-probability sampling, namely total sampling or saturated samples of 49 respondents. Data analysis uses descriptive statistics (mean) and non-parametric inference (Mann-Whitney U test) with the help of SPSS software. The results of the study showed that there were no differences in conflict tactics between male and female groups. Meanwhile, based on worker status, there were differences in conflict tactics between civil servants and non-civil servants in rational persuasive tactics, legitimacy and rational requests. Finally, only the co-opting tactic showed significant differences between the Bachelor and Non-Bachelor education groups.